2011
DOI: 10.1017/s1047951111001478
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Eisenmenger syndrome with ventricular septal defect using equivalent electronic system

Abstract: Our model is effective and available for simulating normal cardiac conditions and cardiovascular diseases, especially the Eisenmenger syndrome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0
4

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 29 publications
0
4
0
4
Order By: Relevance
“…That is to say, the value of resistance R ltor is inverse to the opening area. The study in [11] observed that the resistance could be 1000 hydraulic resistance unit for normal and greatly reduced to 0.15 unit for large VSD. Authors are inspired by the nonlinear relation between mitral resistance and corresponding area, which was proposed by Beyer et al [48].…”
Section: Ph Caused By Ventricular Septal Defectmentioning
confidence: 98%
See 2 more Smart Citations
“…That is to say, the value of resistance R ltor is inverse to the opening area. The study in [11] observed that the resistance could be 1000 hydraulic resistance unit for normal and greatly reduced to 0.15 unit for large VSD. Authors are inspired by the nonlinear relation between mitral resistance and corresponding area, which was proposed by Beyer et al [48].…”
Section: Ph Caused By Ventricular Septal Defectmentioning
confidence: 98%
“…The simulation results showed that abnormal LV diastolic performance alone can result in decreased LV and right ventricular (RV) systolic performance [10]. Besides, Korurek et al simulated Eisenmenger syndrome with ventricular septal defect [11]. It was found that there was a remarkable increase in the pulmonary artery pressure and RV pressure, but decrease in LV pressure, aortic pressure, aortic flow and pulmonary compliance.…”
Section: Associate Editor Enrique Lara-pezzi Oversaw the Review Of Thmentioning
confidence: 99%
See 1 more Smart Citation
“…Dinlenme esnasında sağ kalp kateterizasyonuyla ölçülen ortalama pulmoner arter basıncında ≥ 25 mmHg artış pulmoner arteriyel hipertansiyon olarak tanımlanır (1) . Atriyal septal defekt, ventriküler septal defekt ve patent duktus arteriyozus gibi yapısal kalp hastalıkları, doğumsal pulmoner arteriyel hipertansiyonun önemli nedenlerindendir (2,3) . Erişkinlerde görülen doğumsal kalp hastalığı olgularında pulmoner arteriyel hipertansiyon prevalansı %5-10 arasında değişmektedir (4) .…”
unclassified
“…Sol-sağ şantlar ve basınç artışı nedeniyle pulmoner yatağın uzun süre yüksek kan akışına maruz kalması pulmoner obstrüktif arteriyopatiye ve sonuçta pulmoner vasküler direnç artışına neden olabilir. Pulmoner vasküler direnç sistemik vasküler dirence yaklaşır ya da onu geçerse şant tersine döner; bu durum Eisenmenger sendromu olarak adlandırılır (2) . Eisenmenger sendromunda düşük pH, düşük arteriyel oksijen satürasyonu ve sekonder eritrositoz dispne, siyanoz ve halsizlik gibi şikayetlerin gelişiminden sorumludur.…”
unclassified